Oxybutynin as an alternative treatment for hyperhidrosis - Sergio Delort; Evaldo Marchi; Marcos Antônio Corrêa (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Hyperhidrosis is the excessive production of sweating, which can be primary and focal or secondary to various pathologies. The exact cause of primary focal hyperhidrosis is still unknown, although a genetic basis is recognized, and its prevalence varies from 1% to 2.8%. The most affected sites are the armpits, palms, soles and face. It causes much discomfort, affects the quality of life, and is estimated to be undervalued by health professionals. Many treatment options are proposed, both clinical and surgical. The aim of this review is to focus on the treatment of hyperhidrosis with oxybutynin, an anticholinergic drug originally used to control overactive bladder.